Classification and surgical treatment of congential biliary dilatation - WANG Jin, WU Shuodong (Waike lilun yu shijian, 2023)
Congential biliary dilitation (CBD) is rare biliary tract disease in clinic. Clinical classification and disease characteristics of CBD is the key of accurate treatment. Surgical treatment was regarded as the first choice for adult patients with CBD including traditional surgery. There is still a controversy in the strategy of reconstruction of bile duct during operation. In this article the progress in diagnosis and treatment of CBD was reviewed.